Cytogenetic analysis of myxoid liposarcoma and myxofibrosarcoma by array-based comparative genomic hybridisation. Issue 9 (2nd June 2006) - Ohguri, T; Hisaoka, M; Kawauchi, S; Sasaki, K; Aoki, T; Kanemitsu, S; Matsuyama, A; Korogi, Y; Hashimoto, H
Abstract : Aim: To investigate overall chromosomal alterations using array-based comparative genomic hybridisation (CGH) of myxoid liposarcomas (MLSs) and myxofibrosarcomas (MFSs). Materials and methods: Genomic DNA extracted from fresh-frozen tumour tissues was labelled with fluorochromes and then hybridised on to an array consisting of 1440 bacterial artificial chromosome clones representing regions throughout the entire human genome important in cytogenetics and oncology. Results: DNA copy number aberrations (CNAs) were found in all the 8 MFSs, but no alterations were found in 7 (70%) of 10 MLSs. In MFSs, the most frequent CNAs were gains at 7p21.1–p22.1 and 12q15–q21.1 and a loss at 13q14.3–q34. The second most frequent CNAs were gains at 7q33–q35, 9q22.31–q22.33, 12p13.32–pter, 17q22–q23, Xp11.2 and Xq12 and losses at 10p13–p14, 10q25, 11p11–p14, 11q23.3–q25, 20p11–p12 and 21q22.13–q22.2, which were detected in 38% of the MFSs examined. In MLSs, only a few CNAs were found in two sarcomas with gains at 8p21.2–p23.3, 8q11.22–q12.2 and 8q23.1–q24.3, and in one with gains at 5p13.2–p14.3 and 5q11.2–5q35.2 and a loss at 21q22.2–qter. Conclusions: MFS has more frequent and diverse CNAs than MLS, which reinforces the hypothesis that MFS is genetically different from MLS. Out-array CGH analysis may also provide several entry points for the identification of candidate genes associated with oncogenesis and progression in MFS.